Tailoring anisotropic thermal conductivity by varying filler particle organization in nickel-polydimethylsiloxane composites. (August 2019) - Tsai, Peiying J; Pal, Souvik; Ghosh, Suvojit; Puri, Ishwar K
Anisotropic properties can be imparted to composite materials by arranging filler particles along specific directions inside the polymer matrix. These anisotropic patterns can be produced through dynamic field-assisted assembly of the filler particles during additive manufacturing. Using finite element analysis, we explore how chainlike arrangements of nickel particles embedded in a polydimethylsiloxane matrix modify bulk thermal conductivities in the axial and transverse directions. The axial conductivity increases up to nine times of the matrix conductivity with increasing filler volume fraction. While the axial conductivity decreases with increasing interparticle spacing, the transverse conductivity is uninfluenced. When particles within a chain are arranged in a zigzag pattern, increasing the interparticle zigzag angle decreases axial conductivity but increases transverse conductivity. As that angle increases to ∼55 º, the axial conductivity approaches a minimum, while the transverse conductivity approaches its maximum. An empirical model that includes effects of interparticle spacing and zigzag angle to predict the anisotropic thermal conductivity of a composite containing particle chains is presented. These results are relevant for the material design of particulate-reinforced polymer composites for advanced field-assisted additive manufacturing strategies.